Formation of the node of Ranvier by Schwann cells is under control of transcription factor Sox10 - Saur, Anna-Lena; Fröb, Franziska; Weider, Matthias; Wegner, Michael (Glia, 2021)
The transcription factor Sox10 is an essential regulator of genes that code for structural components of the myelin sheath and for lipid metabolic enzymes in both types of myelinating glia in the central and peripheral nervous systems. In an attempt to characterize additional Sox10 target genes in Schwann cells, we identified in this study a strong influence of Sox10 on the expression of genes associated with adhesion in the MSC80 Schwann cell line. These included the genes for Gliomedin, Neuronal cell adhesion molecule and Neurofascin that together constitute essential Schwann cell contributions to paranode and node of Ranvier. Using bioinformatics and molecular biology techniques we provide evidence that Sox10 directly activates these genes by binding to conserved regulatory regions. For activation, Sox10 cooperates with Krox20, a transcription factor previously identified as the central regulator of Schwann cell myelination. Both the activating function of Sox10 as well as its cooperation with Krox20 were confirmed in vivo. We conclude that the employment of Sox10 and Krox20 as regulators of structural myelin sheath components and genes associated with the node of Ranvier is one way of ensuring a biologically meaningful coordinated formation of both structures during peripheral myelination.
CRIS-Team Scopus Importer:2021-03-05
Keywords: glia; HMG; Krox; node of Ranvier; Schwann cell; Sox